2010
DOI: 10.2106/jbjs.i.00332
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Radial Head Resection Following Isolated Radial Head Fractures in Patients Younger Than Forty Years Old

Abstract: Radial head resection in young patients with isolated fractures without instability yields long-term satisfactory results in >90% of cases. Osteoarthritic changes are uniformly present but typically are not associated with functional impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
74
1
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(90 citation statements)
references
References 24 publications
5
74
1
10
Order By: Relevance
“…We favor resection over reconstruction in severely comminuted radial head fractures where anatomical fixation cannot be achieved. This is in accordance with multiple studies which concluded that resection of radial head provided satisfactory pain relief and functional range of motion [17][18][19][20][21][22][23]. In our study 80% patients returned to their previous occupation regardless of procedure done.…”
Section: Discussionsupporting
confidence: 93%
“…We favor resection over reconstruction in severely comminuted radial head fractures where anatomical fixation cannot be achieved. This is in accordance with multiple studies which concluded that resection of radial head provided satisfactory pain relief and functional range of motion [17][18][19][20][21][22][23]. In our study 80% patients returned to their previous occupation regardless of procedure done.…”
Section: Discussionsupporting
confidence: 93%
“…Common treatment options of Mason type III fractures are osteosynthesis, radial head resection and prosthetic replacement. Radial head resection leads to predominantly good results in stable elbows without further concomitant lesions [1]. An incorrect indication for resection will lead to persistent valgus, longitudinal forearm instability and other secondary symptoms [1,12,13,25].…”
Section: Introductionmentioning
confidence: 99%
“…Our results are supported by a study conducted by Karlsson et al [8] that evaluated isolated comminuted radial head fractures; this study found that the mean range of motion deficit in the elbow was 5°-10°. In addition, good to excellent results according to the Mayo Elbow Performance Index were reported by Antuña et al [9] in a review of 26 patients treated with primary radial head excision who were followed up for a minimum of 15 years. However, Swanson et al [24] presented a clear sequence of events when a loss of radiocapitellar contact resulted in lateral elbow instability, arthritis, loss of strength and motion, and ulnar nerve symptoms.…”
Section: Discussionmentioning
confidence: 91%
“…[5,6] Although biological treatment modalities, such as conservative methods and open reduction and internal fixation, are first-choice treatments, [7] especially for Mason Type-III fractures, the optimum treatment method remains controversial. [5,6] Results of radial head resection (RHR) [8,9] and radial head prosthesis…”
mentioning
confidence: 99%